Psychological correlates of fatigue in rheumatoid arthritis: A systematic review. (July 2015) - Matcham, F.; Ali, S.; Hotopf, M.; Chalder, T.
Abstract: Fatigue is common and debilitating in Rheumatoid Arthritis (RA). A focus on the psychological variables associated with fatigue may help to identify targets for intervention which could enhance the treatment of fatigue in RA. The purpose of this review was to systematically identify psychological variables related to fatigue in RA, with the overall aim of suggesting evidence-based targets for fatigue intervention in RA. Twenty-nine studies met inclusion criteria and were included in the narrative synthesis. A wide range of psychological variables were addressed, spanning 6 categories: affect and common mental disorders; RA-related cognitions; non-RA-related cognitions; personality traits; stress and coping; and social support/interpersonal relationships. The most consistent relationship was found between mood and fatigue, with low mood frequently associated with increased fatigue. Some evidence also highlighted the relationship between RA-related cognitions (such as RA self-efficacy) and fatigue, and non-RA-cognitions (such as goal ownership) and fatigue. Limited evidence was found to support the relationship between stress and coping or personality traits and fatigue, although mixed evidence was found for the relationship between social support and fatigue. The results of this review suggest the interventions for fatigue in RA may benefit from a focus on mental health, and disease-related cognitions. Highlights: Systematic review of the psychological associates of fatigue in RA. Reduced mood frequently associated with increased fatigue. Some evidence for an association between RA-related cognitions and fatigue. Limited evidence for an associated between stress and personality and fatigue. Suggested intervention targets include mental health and RA-related cognitions.